Genome-wide identification and characterization of 14-3-3 gene family related to negative regulation of starch accumulation in storage root of Manihot esculenta - Pan, Ranran; Wang, Yajie; An, Feifei; Yao, Yuan; Xue, Jingjing; Zhu, Wenli; Luo, Xiuqin; Lai, Hanggui; Chen, Songbi (Frontiers in Plant Science, 2023)
The 14-3-3 protein family is a kind of highly conservative member of acid protein family, which plays an important role in regulating a series of important biological activities and various signal transduction pathways. The role of 14-3-3 proteins in regulating starch accumulation still remains largely unknown. To investigate the properties, the structures of Me14-3-3 proteins, their functions involved in starch accumulation in storage roots, and sixteen Me14-3-3 genes were identified. Phylogenetic analysis revealed that the Me14-3-3 family proteins are split into two groups (ε and non-ε groups). All the Me14-3-3 proteins contain nine antiparallel a-helices. The Me14-3-3s-GFP fusion protein was targeted exclusively to the nuclei and cytoplasm. In the early stage of starch accumulation in the storage, the Me14-3-3 genes were highly expressed in high-starch cultivars, while in the late stage of starch accumulation, the Me14-3-3 genes were highly expressed in low-starch cultivars. The Me14-3-3 I, II, V, and XVI had a relatively high expression levels in the storage roots. The transgenic evidences from Me14-3-3II overexpression in Arabidopsis thaliana and the virus-induced gene silencing (VIGS) in cassava leaves and storage roots suggests that Me14-3-3II is involved in the negative regulation of starch accumulation. This study provides a new insight to understand the molecular mechanisms of starch accumulation linked with Me14-3-3 genes during cassava storage root development.